The Effect of Motivation, Competence and Work Environment to the Management of Goods as a Regional Asset Manager in Padang City - Eliza, Yulina; Putri, Viona; Hasbullah, Hendri; Luthfi, Mohammad (International Journal of Management Excellence (ISSN: 2292-1648), 2019)
This study aims to determine the effect of motivation, competence and work environment on improving the performance of goods administrators as employees of regional asset management in Padang City. The object of this research is the Management of Goods within the Padang City Government with studies conducted at the Regional Financial and Asset Management Agency. The total population is 481 people who manage goods, samples taken as many as 120 people randomly. Instrument testing is done by validity test and reliability test. Data analysis using multiple linear regression analysis and hypothesis testing. The results of this study found that motivation, competence and work environment had a significant effect on the performance of goods administrators as employees of asset management in the Padang City Government environment.